Ghana : Fifth and Sixth Reviews Under the Extended Credit Facility, Request for Waivers for Nonobservance of Performance Criteria, and Request for Modification of Performance Criteria-Press Release; Staff Report; and Statement by the Executive Director for Ghana. (IMF Staff Country Reports; Country Report ;, 2018)
Program performance improved in 2017 and macroeconomic conditions have strengthened considerably. Growth increased on the back of expanded oil production; inflation declined; the fiscal deficit was significantly reduced, leading to a primary surplus for the first time in fifteen years; the exchange rate regained stability; and the external position improved, with a large reserve build-up. Challenges remain, though, as a still elevated (albeit declining) debt burden and the economy's exposure to risks limit policy space; and progress in meeting structural benchmarks remains mixed. Program discussions focused on policies to lock in recent gains to secure continued stability and progress beyond the Fund-supported program (in line with the authorities' goal of "irreversibility" of sound policies).